FRI0370 Efficacy and safety of lesinurad (RDEA594), a novel URAT1 inhibitor, in combination with allopurinol in allopurinol-refractory gout patients: Results from a randomized, blinded, placebo-controlled, phase 2b extension study. (23rd January 2014) - Perez-Ruiz, F.; Sundy, J.; Krishnan, E.; Hingorani, V.; Welp, J.; Rodgers, T.; Manhard, K.; Cravets, M.; Hagerty, D.; Quart, B.
Abstract : Background: Lesinurad (LESUR) is an oral investigational URAT1 inhibitor for the treatment of gout. A Phase 2B study in 208 gout patients with an inadequate response to allopurinol (ALLO) (200-600 mg/day for ≥6 weeks) demonstrated that the combination of LESUR+ALLO resulted in superior reductions in sUA with 79%, 74%, and 63% of patients achieving sUA <6 mg/dL after 28 days of dosing with 600 mg, 400 mg and 200 mg LESUR, respectively, compared to 25% with placebo (PBO)+ALLO (p<0.0001 for all comparisons). Subjects completing the Phase 2B study could enter a 44-week, blinded, PBO-controlled extension, the results of which are presented here. Objectives: To assess the ongoing efficacy and safety of LESUR in combination with ALLO vs. PBO+ALLO in patients with an inadequate response to standard doses of ALLO. Methods: Subjects completing the double-blind 28-day main study were washed out of LESUR or PBO before entering the blinded extension period, but remained on a stable dose of ALLO. Subjects then restarted their original blinded treatment of LESUR or PBO. All LESUR-treated subjects started on the 200 mg dose and were to have the dose titrated stepwise to 400 or 600 mg if the sUA was not <5 mg/dL. After dose escalation of LESUR or PBO, ALLO dose could be escalated. Results: 126 subjects enrolled into the blinded extension study (78 LESUR and 48 PBO); 91 subjects completed 44 weeks at time of this analysis. 78% of LESUR treated subjects maintained sUA <6 mg/dL at 44 weeks, compared to 56% of PBO subjects (LOCF analysis); 59% of subjects receiving LESUR also achieved sUA<5 mg/dL compared to 25% of PBO subjects. ALLO doses were increased in the majority of PBO subjects. 29 subjects (13 PBO/16 LESUR) withdrew from the study for any reason before Week 44. Overall rates of adverse events (AEs) were low and similar between the treatment groups. 4 subjects reported serious AEs (angina pectoris, cerebral artery embolism, tendon rupture, bursitis infective) considered not related to treatment. Transient serum creatinine (sCr) elevations were observed in both groups; on LESUR these generally occurred early or after dose escalations and usually resolved to within the normal range while on LESUR. 4 subjects discontinued due to increased sCr; 1 receiving PBO and 3 on LESUR. Monthly gout flare rates for subjects remaining on the 200 mg dose were generally lower for the LESUR group compared to PBO during Months 7-12. Conclusions: In patients who do not respond adequately to ALLO, the addition of LESUR produced consistent, sustained reductions in sUA levels, with the majority of subjects achieving sUA levels of <6 mg/dL and <5 mg/dL. Despite dose increases of ALLO in the majority of PBO subjects, combination therapy was superior. LESUR was well-tolerated with a similar rate of AEs to placebo. The premature discontinuation rate on PBO was higher than on LESUR. LESUR is a promising investigational drug for the treatment of hyperuricemia in gout patients. Disclosure of Interest: F. Perez-Ruiz Grant/Research support from: Asociaciόn de Reumatόlogos del Hospital de Cruces y Ministerio de Sanidad, Gobierno de España, Consultant for: Ardea Biosciences, Menarini Pharma, Novartis, Savient, Speakers Bureau: Menarini Pharma, Novartis, J. Sundy Grant/Research support from: Ardea Biosciences, Nuon Therapeutics, Pharmos, Regeneron, Celgene, Savient, Abbot, Jansen, Consultant for: Ardea Biosciences, Nuon Therapeutics, Pharmos, Novartis, Savient, Roche, E. Krishnan Grant/Research support from: Takeda, Consultant for: Takeda, V. Hingorani Consultant for: Ardea Biosciences, J. Welp Employee of: Ardea Biosciences, T. Rodgers Employee of: Ardea Biosciences, K. Manhard Employee of: Ardea Biosciences, M. Cravets Employee of: Ardea Biosciences, D. Hagerty Employee of: Ardea Biosciences, B. Quart Employee of: Ardea Biosciences